Investigating design issues in mobile computer-mediated communication technologies - Ogara, Solomon O.; Koh, Chang (Taylor & Francis, 2015)
Mobility is the new reality of business and stands to have a significant impact on the implementation of mobile computermediated communication (mCMC), such as mobile texting, mobile video, and mobile presence. Information systems researchers are faced with the challenge of how to design these artifacts to maximize the benefits of social interaction among potential communication partners. We develop a theoretical model that examines the relationship between user experience, perceived richness, perceived social presence, interactivity, and satisfaction in mCMC. Findings suggest that user experience, perceived richness and interactivity are important in the design of social presence in mCMC. Both social presence and perceived richness influenced user satisfaction with mCMC. The influence is greater in mobile instant messaging than mobile texting.
Keywords: user experience; social presence; user satisfaction; media richness; interactivity; computer-mediated communication